2023
DOI: 10.1093/cercor/bhad168
|View full text |Cite
|
Sign up to set email alerts
|

Dual-stream cortical pathways mediate sensory prediction

Abstract: Predictions are constantly generated from diverse sources to optimize cognitive functions in the ever-changing environment. However, the neural origin and generation process of top-down induced prediction remain elusive. We hypothesized that motor-based and memory-based predictions are mediated by distinct descending networks from motor and memory systems to the sensory cortices. Using functional magnetic resonance imaging (fMRI) and a dual imagery paradigm, we found that motor and memory upstream systems acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…This result suggests that the motor simulation stream may also be solicited during inner hearing, but to a lesser extent than during inner speaking (consistent with the results obtained by Tian et al, 2016). 4 By contrasting inner speaking and inner hearing of non-speech sounds, Chu et al (2023) recently showed a clear dissociation in the involvement of the motor-based and memory-based networks, further supporting the distinction between these two processes. Overall, our results are also compatible with the framework recently provided by Pratts et al (2023), in which inner speech can be generated by two separate mechanisms similar to those postulated by the dual stream prediction model, according to the intentionality and egocentricity constraints of the task.…”
Section: Discussionsupporting
confidence: 77%
“…This result suggests that the motor simulation stream may also be solicited during inner hearing, but to a lesser extent than during inner speaking (consistent with the results obtained by Tian et al, 2016). 4 By contrasting inner speaking and inner hearing of non-speech sounds, Chu et al (2023) recently showed a clear dissociation in the involvement of the motor-based and memory-based networks, further supporting the distinction between these two processes. Overall, our results are also compatible with the framework recently provided by Pratts et al (2023), in which inner speech can be generated by two separate mechanisms similar to those postulated by the dual stream prediction model, according to the intentionality and egocentricity constraints of the task.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, human fMRI studies based on the mental imagery paradigm also investigate the PP mechanism within cortico-cortical interactions associated with declarative memory (Chu et al, 2023;Ortiz-Tudela et al, 2023). These studies support the differentiated mechanism between memory and motor-based predictions (Chu et al, 2023), and episodic and semantic predictions (Ortiz-Tudela et al, 2023).…”
Section: Declarative Memorymentioning
confidence: 60%
“…Meanwhile, in episodic recall descending neurons from the hippocampus can be routed via a disinhibitory pathway, which helps facilitate selective neocortical reinstatement that supports memory recall (Barron et al, 2020). Furthermore, human fMRI studies based on the mental imagery paradigm also investigate the PP mechanism within cortico-cortical interactions associated with declarative memory (Chu et al, 2023;Ortiz-Tudela et al, 2023). These studies support the differentiated mechanism between memory and motor-based predictions (Chu et al, 2023), and episodic and semantic predictions (Ortiz-Tudela et al, 2023).…”
Section: Declarative Memorymentioning
confidence: 73%
“…Our model, based on two distinct modulatory functions in the motor-to-sensory transformation, assumes two types of predictions that can presumably integrate both inference models. EC serves as a content prediction, resembling the strong priors that would elicit the specific auditory neural representation without corresponding external stimulation [4,8,35,36]. Whereas, CD serves as a prediction for agency, and the impairment would cause the failure to explain away the internally generated auditory neural representations that are evoked by EC [49,52,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…For example, action-induced enhancement has been found in a subset of sensory cortices in addition to action-induced suppression [30][31][32][33][34]. Auditory neural representations are constructed in auditory working memory based on covert speaking [8,35,36]. This motor-based auditory working memory (i.e.…”
Section: Introductionmentioning
confidence: 99%